Peluang Pengembangan Atraksi Wisata di Daya Tarik Wisata Pantai Soka Tabanan, Bali. - Ni Gusti Ayu Kadek Silviani; I Nyoman Sunarta (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2021)
Soka Beach is one of the tourist attractions in Tabanan Regency. This study aims to determine the potentials possessed by the attractiveness of Soka Beach, both natural and cultural potentials that are still maintained today. After knowing the existing potential, a work plan from the government, the community, and the manager of the Soka Beach attraction is needed to find out the opportunities for developing attractions at the Soka Beach attraction.In this study using qualitative data, while the data sources used are primary and secondary data sources. Data collection techniques in this study using observation, interview, and documentation techniques. In this study using qualitative data, while the data sources used are primary and secondary data sources. Data collection techniques in this study using observation, interview, and documentation techniques. Judging from the potential and work plans of the government, the community, and the manager of the Soka Beach attraction, this attraction has a pretty good opportunity in developing tourist attractions.Keywords: Opportunities, tourism potential, tourism development.